"I be trying" [compact disc] - Burnside, Cedric (Single Lock Records, 2021)
The ultimate statement of purpose for a critically acclaimed artist who has proudly carried the mantle of Mississippi Hill Country blues around the world. Over thirteen tracks, Burnside delivers his bruised but unfettered truth over blistering guitar and deep pocket drums--a sound birthed in his soul but developed and perfected on the road.